Innovations in Land Rights Recognition, Administration, and Governance - Deininger, Klaus (World Bank, 2012)
The eight Millennium Development Goals (MDGs) form a blueprint that is agreed to by all the world's countries and its leading development institutions. The first seven goals are mutually reinforcing and are directed at reducing poverty in all its forms. The last goal, global partnership for development, is about the means to achieve the first seven. To track the progress in achieving the MDGs a framework of targets and indicators has been developed. This framework includes 18 targets and 48 indicators enabling the ongoing monitoring of the progress that is reported on annually (United Nations, or UN 2000). The contribution of land professionals to achieving the MDGs is central and vital. The provision of relevant geographic information in terms of mapping and databases of the built and natural environments, as well as providing secure tenure systems, systems for land valuation, land use management and land development are all key components of the MDGs. Land professionals have an important role in directing land administration systems in support of secure property rights, in particular for those who have traditionally been disadvantaged, of efficient land markets, and of effective land use management. These functions underpin development and innovation and form the 'backbone' in society that supports social justice, economic growth, and environmental sustainability. Simply, no development will take place without having a spatial dimension, and no development will happen without the footprint of the land professionals.